PRETREATMENT WITH ONDANSETRON IN PREVENTION OF PAIN ON PROPOFOL INJECTION - Sharma Regmi, Bharati Devi; Deo , Gopendra Prasad; Gyawali , Madhu; Adhikari , Kiran; Regmi , Subi (Journal of Chitwan Medical College, 2022)
Background: Pain on intravenous injection of propofol is seen in almost 70% of patients without any pretreatments. This study was conducted to evaluate the effect of ondansetron in reducing the occurrence of pain on intravenous injection of propofol. Methods: Two hundred and thirty-two patients aged between 18- 60 years of either sex belonging to ASA status I and II, scheduled for laparoscopic cholecystectomy under general anesthesia at Chitwan Medical College, Bharatpur, Nepal, from from September 1, 2020 to March 31, 2021 were recruited in this study. They were assigned randomly into two groups with 116 participants in each, where Group 1 received 2 ml (4 mg) of ondansetron and Group 2 received 2 ml of 0.9% saline (placebo) intravenously as the pretreatment solution prior to injection of propofol for induction of general anesthesia. The overall incidence of pain in the saline group was 84.5% compared to 48.3% in the ondansetron group (P < 0.001). Result: Pain was of mild intensity in most patients who belonged to the ondansetron group (33.6%) whereas it was of moderate intensity in most participants of the saline group (54.3%). Few patients in the study group experienced severe pain (0.9%) as compared to the placebo group (9.5%) with P < 0.001. Conclusion: Therefore, it was concluded that pretreatment with ondansetron may be a useful intervention in reducing the incidence of pain on intravenous propofol administration without any adverse effects in significant number of patients.